Couple therapy following prostate cancer surgery: a manual to guide treatment. (28th June 2016) - Forbat, Liz; Robertson, Jane; McNamee, Phillip
Abstract: Prostate cancer is the third most common cancer in the UK. Ten‐year survival is high; consequently a service priority is addressing survivorship issues to support men living with the longer‐term consequences of the disease and its treatments. This paper presents a treatment manual which has been tested with couples following prostate cancer surgery to decrease distress in sexual functioning, and improve relational functioning. The content of the manual is described alongside a fictionalized case vignette that illustrates the content and process of sessions. The paper presents the RIPSToP Model (R elatI onalPS ychosexualT reatment for couples withP rostate cancer). The manual was developed and piloted in a mixed‐method feasibility and acceptability randomized pilot control trial. Qualitative interviews with clinicians delivering the intervention indicate that the manual was acceptable. Practitioner points: A systemic manual for supporting couples after prostate cancer surgery has been developed The manual presents a new model, derived from the literature, focusing on family context and the couple dynamic The model impacts psychological wellbeing, relationship functioning and distress related to sexual functioning Practitioners reported positive views of the manual and adhered to its content and structure